Assessing the Effectiveness of Local Government Roles in the Development of Sungai Batang Village Tourism, Agam Regency - Rafi Anriyan; Asdi Agustar; Widya Fitriana (NeoRespublica : Jurnal Ilmu Pemerintahan, 2026)
Tourism is one of the priority sectors for development in Indonesia, as it is seen as having a multiplier effect and the potential to improve the economy, including in rural areas. In this regard, developing tourist villages is one of the strategies implemented. This research aims to determine the role of the regional government of Nagari Sungai Batang, Agam Regency, West Sumatra Province. This research is descriptive in nature with a qualitative approach. The main data come from informants consisting of government officials at the district and Nagari levels, tourism business actors, and tourists. The research results show that the district government and Nagari government have played a role in developing the Sungai Batang Tourism Village, but the role they have played is still not optimal. As facilitators, they have not been able to provide adequate infrastructure and supporting facilities to develop tourist attractions. The knowledge, skills, and interests of community members have not been adequately facilitated and mobilized, so their involvement in utilizing their potential is not yet optimal.  The conclusion of the study is that the government has played a role in the development of the tourism village, but there is still a need for capacity building, strengthening the facilitator role, infrastructure development, and enhancing community involvement so that the potential of Sungai Batang Tourism Village can be maximized sustainably.